Can anti-Müllerian hormone be predictive of spontaneous onset of pregnancy in women with unexplained infertility?. (November 2013) - Casadei, L.; Manicuti, C.; Puca, F.; Madrigale, A.; Emidi, E.; Piccione, E.
Abstract : The objective of the study was to assess anti-Müllerian hormone's (AMH) role in predicting spontaneous onset of pregnancy. This observational cohort study included 83 women with unexplained infertility and normal or low ovarian reserve. Serum AMH, FSH, LH, 17β-oestradiol, inhibin B levels were measured and the number of early antral follicles (2–9 mm) was evaluated on days 2–5 of the cycle. Spearman's correlation was used for comparison of strength of correlation. The diagnostic power of AMH in predicting spontaneous pregnancy was evaluated by receiver operating characteristic (ROC) curves. Markers of ovarian reserve in pregnant women and women without pregnancy were similar. In the entire study population, any markers (AMH, FSH, AFC, age), correlated with each other, but no marker was correlated with pregnancy. The area under the ROC curve for AMH reached a value of 0.385 ± 0.07 (0.25–0.52, 95% confidence interval, CI); for FSH 0.415 ± 0.08 (0.25–0.58, 95% CI); for AFC 0.418 ± 0.08 (0.26–0.57, 95% CI), for age 0.496 ± 0.08 (0.34–0.65, 95% CI). The study did not find a predictive role for AMH in predicting spontaneous onset of pregnancy. Even when AMH levels are very low, a spontaneous pregnancy may still occur.